DEVELOPMENT OF SUSTAINABLE AND SOCIALLY RESPONSIBLE BUSINESS IN LITHUANIA IN THE EUROPEAN AND WORLDWIDE CONTEXT - Ruževičius, Juozas (Ekonomika, 2009)
This article analyses the peculiarities, interrelations and development of two relatively new concepts of organizational development – socially responsible and sustainable business. Socially responsible business, which adopts the sustainable development concept, more and more often requires than adequate behaviour of the supply chain partners. The complex of tools to achieve socially responsible and sustainable business – SA 8000 (Social Accountability), Global Compact, OHSAS 18001 (Occupational Health and Safety Assessment Series), ISO 14001, EMAS (Eco-Management and Audit Scheme), FSC (Forest Stewardship Council), eco-labelling, etc. – can be integrated into one organization. The paper provides an analysis of the development of these systems in Lithuania within the context of the European and global business. The interrelations of different management systems, the links among them, integration possibilities and improvement propositions are described.